The Testosterone Trials: Seven coordinated trials of testosterone treatment in elderly men. (June 2014) - Snyder, Peter J; Ellenberg, Susan S; Cunningham, Glenn R; Matsumoto, Alvin M; Bhasin, Shalender; Barrett-Connor, Elizabeth; Gill, Thomas M; Farrar, John T; Cella, David; Rosen, Raymond C; Resnick, Susan M; Swerdloff, Ronald S; et al.
Background: The prevalence of low testosterone levels in men increases with age, as does the prevalence of decreased mobility, sexual function, self-perceived vitality, cognitive abilities, bone mineral density, and glucose tolerance, and of increased anemia and coronary artery disease. Similar changes occur in men who have low serum testosterone concentrations due to known pituitary or testicular disease, and testosterone treatment improves the abnormalities. Prior studies of the effect of testosterone treatment in elderly men, however, have produced equivocal results. Purpose: To describe a coordinated set of clinical trials designed to avoid the pitfalls of prior studies and to determine definitively whether testosterone treatment of elderly men with low testosterone is efficacious in improving symptoms and objective measures of age-associated conditions. Methods: We present the scientific and clinical rationale for the decisions made in the design of this set of trials. Results: We designed The Testosterone Trials as a coordinated set of seven trials to determine if testosterone treatment of elderly men with low serum testosterone concentrations and symptoms and objective evidence of impaired mobility and/or diminished libido and/or reduced vitality would be efficacious in improving mobility (Physical Function Trial), sexual function (Sexual Function Trial), fatigue (Vitality Trial), cognitive function (Cognitive Function Trial), hemoglobin (Anemia Trial), bone density (Bone Trial), and coronary artery plaque volume (Cardiovascular Trial). The scientific advantages of this coordination were common eligibility criteria, common approaches to treatment and monitoring, and the ability to pool safety data. The logistical advantages were a single steering committee, data coordinating center and data and safety monitoring board, the same clinical trial sites, and the possibility of men participating in multiple trials. The major consideration in participant selection was setting the eligibility criterion for serum testosterone low enough to ensure that the men were unequivocally testosterone deficient, but not so low as to preclude sufficient enrollment or eventual generalizability of the results. The major considerations in choosing primary outcomes for each trial were identifying those of the highest clinical importance and identifying the minimum clinically important differences between treatment arms for sample size estimation. Potential limitations: Setting the serum testosterone concentration sufficiently low to ensure that most men would be unequivocally testosterone deficient, as well as many other entry criteria, resulted in screening approximately 30 men in person to randomize one participant. Conclusion: Designing The Testosterone Trials as a coordinated set of seven trials afforded many important scientific and logistical advantages but required an intensive recruitment and screening effort.